Group decision-making processes in teams guided by Agile principles - Yushchenko, Olha; Hájek, Jiří; Krupa, Miroslav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
Interest in agile methodologies is growing across many industries. Scrum methodology is undoubtedly the most used agile framework. The decision-making process in Scrum teams is complex and can be affected by various factors. Inspired by theories and models of consensus-based group decision-making, the aim of the diploma thesis was to determine the coping strategy used by Scrum teams to subdue the decision-making challenges and to resolve conflicts that occur during the decision-making process. The research determined three categories of factors which contribute to the creation of a favorable environment for reaching consensus during the decision-making process. Furthermore, results showed that consensus between various stakeholders is facilitated by the Product Owner, while consensus on the level of the team is built by the Scrum Master. The decision-making challenges that Scrum teams face were then examined in the light of the corresponding Scrum principles. This thesis contributes to current theory on decision-making in Scrum teams and proposes to expand the description of the Scrum Master responsibilities to reflect the Scrum Master’s role in cognitive conflict facilitation and the team’s consensus building.
Vedoucí práce: Jiří Hájek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses